KORELASI NILAI KADAR KARBON DENGAN ESTIMASI PRODUKTIFITAS PADI SAWAH VULKANIS GUNUNG TALANG - Siska Amelia; Dian Fiantis; Syafrimen Yasin (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Organic carbon contributes to increasing soil productivity. In determining the soil fertility indicators, soil organic carbon mapping is required to provide information and demonstrate the distribution of organic carbon. In this study, remote sensing method testing was carried out by comparing data between observations in the field with rice productivity estimation data using Landsat 8 imagery. The observation was conducted on paddy fields with an area of about 4,800.86 ha in the volcanic region of Mount Talang. This research used a survey method with a grid system of 1,000 x 1,000 m intervals with a soil depth of 0-20 cm and 20-40 cm. The parameters of the soil observations carried out were bulk density, pH, and organic carbon. The results showed that Mount Talang volcanic rice fields had an estimated soil organic carbon stock of ±6,426.118 tons. A weak correlation was obtained between organic carbon and the estimated value of paddy rice productivity (r  =0.024). Hence organic carbon in the study area could not be estimated with the value of lowland rice productivity.